Laterallyloaded piles in multi-layered soils - M. Cao (Lowland Technology International, 2017)
The paper presents a rigorous analytical method, using the theory of the transfer matrix method for calculating the laterally loaded piles in multi-layered soils. Following the technique proposed by Muki and Sternberg, the problem is decomposed into extended layered soils and a fictitious pile characterized respectively by Young’s moduli of the layered soils and those of the differences between the piles and the layered soils. The unknown bending moments along the fictitious pile are determined by solving a Fredholm integral equation of the second kind, which imposes the compatibility condition that the lateral displacements of the fictitious pile are equal to those corresponding to the centroidal axe of the extended layered soils. The pile lateral displacement and slope distributions can be calculated based on the determined fictitious pile bending moment distribution. Selected results from parametrical studies are presented to confirm the validity of the proposed approach and to portray the influence of the governing parameters on the pile bending moment, displacement and slope distributions.